Tensile, three-point bending and impact strength of 3D printed parts using PLA and recycled PLA filaments: A statistical investigation - ATAKÖK, GÜRCAN (My University, 2022)
In this study, the Taguchi methodology was used to investigate the effects of Fused Deposition Modeling (FDM) production parameters tensile strength, three-point bending strength, and impact strength of three-dimensional (3D) printed polylactic acid (PLA) and recycled polylactic acid (Re-PLA) test parts. As FDM process parameters, filaments (PLA, RePLA), three different layer thicknesses (0.15-0.20-0.25 mm), occupancy rates (30%, 50% and 70%), and filling structure (Rectilinear) were determined in the experimental design. The FDM technique was used to print the test parts. The tensile, three-point bending, and impact strength of the test parts were determined using the ISO 527, ISO 180, and ISO 178 test standards, respectively. The results showed that layer thickness is the most efficient factor for improving tensile strength, three point bending strength, and impact strength rather than occupancy rate or filament materials. The optimum results were obtained in layer thickness (0.25 mm), occupancy rate (70%), and filament material (PLA), respectively. They were calculated to be as 60.006 MPa at tensile strength, 125.423 MPa at three-point bending strength, 16.961 kJ/m2 at izod impact strength. Also, Scanning Electron Microscopy (SEM) has been utilized to investigate the morphology and topography alterations in the fractured surface of test parts. The study demonstrates the possibility of 3DP with RePLA filament and environmental awareness was noted by using recycled filament. The study demonstrates the possibility of 3DP with Re-PLA filament and environmental awareness was noted by using recycled filament. The research shows that 3D printing with Re-PLA is feasible. (c) 2022 The Authors. Published by Elsevier B.V.
Keywords: Makina Mühendisliği; Konstrüksiyon ve İmalat; Bilgisayar Destekli Tasarım ve İmalat; Mühendislik ve Teknoloji; Mechanical Engineering; Construction and Manufacturing; Computer Aided Design and Manufacturing; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, MEKANİK; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, MECHANICAL; Automotive Engineering; Computational Mechanics; Physical Sciences; FDM; Re-PLA; Taguchi; Three-point bending strength; SEM; MECHANICAL-PROPERTIES; DIMENSIONAL ACCURACY; PROCESS PARAMETERS; OPTIMIZATION; QUALITY; POLYMER